2018
DOI: 10.2337/db17-1034
|View full text |Cite
|
Sign up to set email alerts
|

ELOVL4-Mediated Production of Very Long-Chain Ceramides Stabilizes Tight Junctions and Prevents Diabetes-Induced Retinal Vascular Permeability

Abstract: Tight junctions (TJs) involve close apposition of transmembrane proteins between cells. Although TJ proteins have been studied in detail, the role of lipids is largely unknown. We addressed the role of very long-chain (VLC ≥26) ceramides in TJs using diabetes-induced loss of the blood-retinal barrier as a model. VLC fatty acids that incorporate into VLC ceramides are produced by elongase elongation of very long-chain fatty acids protein 4 (ELOVL4). ELOVL4 is significantly reduced in the diabetic retina. Overex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 52 publications
(60 reference statements)
3
45
0
Order By: Relevance
“…This is the first report to measure VLC‐PUFA levels in human diabetic retinas, and we observed a decreasing trend in VLC‐PUFA levels and n‐3/n‐6 VLC‐PUFA ratios in diabetic retinas in comparison to age‐matched control retinas. In correlation with our study, Kady et al . reported that intravitreal delivery of human ELOVL4 reduced the diabetes‐induced increase in vascular permeability, thereby increasing VLC‐ceramides in diabetes.…”
Section: Discussionsupporting
confidence: 92%
“…This is the first report to measure VLC‐PUFA levels in human diabetic retinas, and we observed a decreasing trend in VLC‐PUFA levels and n‐3/n‐6 VLC‐PUFA ratios in diabetic retinas in comparison to age‐matched control retinas. In correlation with our study, Kady et al . reported that intravitreal delivery of human ELOVL4 reduced the diabetes‐induced increase in vascular permeability, thereby increasing VLC‐ceramides in diabetes.…”
Section: Discussionsupporting
confidence: 92%
“…To see whether the protective effect of SPL-kd under inflammatory conditions correlates with a change in certain sphingolipid subspecies, a more extended analysis of sphingolipids was performed by LC-MS/MS (Figure 8 and Table S1). Previous studies demonstrated that not only S1P, but also other sphingolipid molecules, such as sphingomyelin [83], ceramides, and very long-chain ceramides [84,85], are involved in endothelial barrier regulation. In agreement with this, other sphingolipid species may mediate the response towards inflammatory stimuli, as we have seen from the LC-MS/MS data that S1P and dihydro-S1P, which are both modestly increased by TNFα in control cells, synergistically increase by TNFα in SPL-kd ( Figure 8).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, dietary manipulations focusing on PUFAs caused a positive impact on pathological retinal neovascularisation in an animal model of oxygen-induced retinopathy. This effect may be related to the role of PUFAs in inflammation [70] or in the synthesis of very-long-chain ceramides, which seem to maintain vascular integrity in experimental diabetes [71].…”
Section: Rise Of the Role Of Lipid Metabolism In Diabetic Complicationsmentioning
confidence: 99%